Laparoscopic approach of excision of anterior abdominal wall actinomycosis - Mark, Satkunan; Firdaus, Mohd; Muselim, Mohd; Rajakumar, Lewellyn (International Surgery Journal, 2021)
Actinomycosis of the abdominal wall is a rare disease. While most of the reported cases are women, we present a 42-year-old male with an abdominal mass for 4 months. Clinical examination of the abdomen revealed a well circumscribed mass in the left iliac fossa. CT abdomen showed an anterior abdominal wall mass with infiltration to the sigmoid colon however colonoscopy ruled out intraluminal origin. In contrast to traditional open approach, a laparoscopic approach was done. The abdominal wall tumour and sigmoid colon was resected en- bloc and continuity restored extra- corporeally through a small incision. Histopathology of the specimen reported an abdominal wall actinomycosis and patient was discharged with antibiotics. Laparoscopic approach was successful as the tumour was small. We therefore conclude that an initial laparoscopic assessment can be advocated and a laparoscopic excision is always possible if the features are favourable.